Kształtowanie się poczucia własnej wartości u dzieci z trudnościami rozwojowymi - Jędrzejowska, Agnieszka (Wydawnictwo Naukowe EDUsfera, 2022)
The general picture of children’s self-esteem may be due to the failures experienced in organized activities or free play of children. The lack of partial or complete realization of demands directed by the teacher or peers often resulted in lowered mood and withdrawal. This represents an important conclusion for those responsible for organizing the educational process in institutions, especially inclusive groups, where it is necessary to take into account the capabilities and limitations of children with developmental difficulties.
Keywords: child; self-esteem; development; developmental difficulties; education